Ocean Acidification Education: Educational Resource Analysis. (20th July 2016) - Lorenzo-Rial, María; Arias-Correa, Azucena; Serrallé-Marzoa, José F.; Álvarez-Lires, María M.
Abstract: This article aims to establish synergies between Science Education, Environmental Education and Marine Science (Campus do Mar), which has already begun, in order to provide ocean acidification education resources for Primary School teachers in pre-service training Global reports, based on emerging ocean acidification science, indicate that this process can be of the same magnitude as climate change; hence its importance to humanity's future. The existing on-line resources have been located, an initial revision of them has been carried out, and a set of analysis categories has been proposed in order to subsequently design educational interventions connecting scientific knowledge, values and attitudes. These will lead to acquiring scientific competence and to acting in favour of the environment as well as developing critical thinking. A collaboration with other institutions has begun to influence non-formal education.